Komunikasi Keluarga Orang Tua Dalam Pengawasan Penggunaan Media Sosial Tiktok Pada Anak Sekolah Dasar - Kartikasari, Fujianthy; Utamidewi, Wahyu; Budhiharti, Tri Widya (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research aims to find out how parents interact with their children in monitoring the use of Tiktok social media, then to find out how children's verbal communication when using Tiktok social media, and also to find out how parents interpret Tiktok social media. This research uses a qualitative method with a descriptive approach, the theory used in this research is low communication theory. In this research, three stages of analysis were also carried out, namely, data reduction, data presentation, and drawing conclusions.The results of this research are that parents tend to use interactions in the categories of active mediation and restrictive mediation. The divergence premise in accommodation theory explains how parents choose communication strategies towards children in terms of supervision. Children tend to use Tiktok according to their own interests, parents' views of the Tiktok application are negative and positive, but parents are aware that technological developments mean that children have to adapt.